The Effect of Regional Industrial Restructuring on the Resource Environmental Carrying Capacity in Jingjiang City, Jiangsu Province, China. (30th September 2020) - Bi, Yunlong; Hu, Yi; Xu, Xiaoli; Niu, Fangqu
Abstract : Disordered industrial expansion in a given region leads to the excessive consumption of resources and environmental deterioration. Therefore, the influence of the regional industrial structure and layout on the resource environmental carrying capacity (RECC) is receiving attention. This study constructs a comprehensive analytical framework of the industries, population, the economy, resources, and the environment. This framework evaluates the importance of each industry with respect to regional socioeconomic development; furthermore, it classifies industries based on the evaluation results and assumes various development scenarios for industrial restructuring. Based on ArcGIS spatial analysis tool, this study analyzes the consumption of resources and the environment in each township under the current development scenario. In addition, this study provides basic support for the optimization of the industrial space layout. The RECC is assessed under different development scenarios, and the results provide a basis for industrial restructuring. The results show that the Jingcheng Subdistrict consumes the most resources and environment among all the township units. However, since it has the highest GDP, it consumes the least resources and the environment per unit GDP overall. The results also show that the RECC with the development of the petroleum, coking, and nuclear fuel processing products industry can maximize the RECC of Jingjiang. The analytical framework in this study effectively connects regional industrial restructuring to the RECC, which can enhance the operability of the decision support.